THE PROBABLE ORIGIN OF LETHAL YELLOWING AND ITS CO¬-IDENTITY WITH OTHER LETHAL DISEASE OF COCONUT - L. Chiarappa (International Coconut Community, 1998)
The working hypothesis is put forward that Lethal Yellowing (LY) disease of coconut originated in Southeast Asia, where the disease is now endemic due to the prevalence of locally resistant to moderately resistant varieties. The suggestion is made that LY is co‑identical with other lethal diseases of coconut characterized by different symptorn expression. These differences are due to certain morphological and physiological characteristics inherent in coconut 'groups' of different origin. A hypothesis is also advanced on the existence of different strains of LY, which would explain the differences in susceptibility of certain varieties when grown in different locations. The need for coordinated research to confirm or reject these hypotheses is discussed.